Effectiveness of virtual reality positive self-talk on changes in brain wave activity among patients with breast cancer undergoing chemotherapy: a randomized controlled trial - Harahap, Ikhsanuddin Ahmad; Nasution, Azizah; Harahap, Urip; Ardinata, Dedi (Jurnal Ners, 2026)
Introduction: Patients with breast cancer undergoing chemotherapy often experience pain, cognitive impairments, and changes in brainwave activity. This study evaluated the efficacy of Virtual Reality Positive Self-Talk (VR-PST) on changes in brain wave activity in breast cancer patients undergoing chemotherapy. Methods: A single-blind randomized controlled clinical trial was conducted involving 92 patients with breast cancer undergoing chemotherapy, who were randomly assigned to the VR-PST intervention group (n = 46) and the control group (n = 46). Participants in the VR-PST group received five intervention sessions conducted over a two-week period, consisting of structured cognitive self-talk presented in a virtual reality environment (VR-PST), while the control group received standard care. Brain wave activities in both groups were measured using the Muse 2 electroencephalographic (EEG) device before and after the intervention. Results: There were shifts in brain waves from delta to alpha waves in both groups, indicating relaxation; however, the VR-PST group showed a more dominant increase in beta waves. The VR-PST group demonstrated a trend toward greater cognitive activation; however, Fisher’s Exact Test showed that the difference between the groups was not statistically significant (p = 0.052). Conclusions: Although the difference was not statistically significant, the observed trend of increased beta-wave activity in the VR-PST group suggests a possible enhancement of cognitive activation. However, this finding should be interpreted with caution, and further studies are required to confirm this effect.